Pre-Service Teacher of PJOK: The Effect of Box Skip Training on Leg Muscle Power - Hudain, Muh. Adnan; Andryawan, Andryawan; Suwardi, Suwardi; Irvan, Irvan; Nurussyariah, Nurussyariah (ETDC: Indonesian Journal of Research and Educational Review, 2024)
This study aims to ascertain the impact of the Box Skip Exercise on the leg muscle power of pre-service teachers at STKIP YPUP Makassar. This study employs an experimental design, specifically a quasi-experimental design. In this study, the population and sample were the pre-service teachers of STKIP YPUP Makassar, with a sample size of 30 people divided into two treatment groups and a control group. We used the t-test to test the research data. The research data that was tested with the t-test shows that the treatment group's data has a calculated T value that is higher than the T table with a value of 9.291>1.753. The significance value of 0.00 falls below 0.05, indicating that box skip exercise has a significant impact on the leg muscle power of physical education pre-service teachers. In contrast, the data from the control group revealed a calculated T value of 3.674, which exceeded the T table by 1.753. Additionally, the significance value of 0.00 was less than 0.05, indicating that the treatment group had a greater influence than the control group. Based on the above data, we can conclude that the treatment group exerted a greater influence than the control group in enhancing the leg muscle power of physical education pre-service teachers at STKIP YPUP Makassar.